Panel data models of new firm formation in New England - Jitendra Parajuli; Kingsley E. Haynes (REGION, 2017)
This study examines the impact of the determinants of new firm formation in New England at the county level from 1999 to 2009. Based on the Spatial Durbin panel model that accounts for spillover effects, it is found that population density and human capital positively affect single-unit firm births within a county and its neighbors. Population growth rate also exerts a significant positive impact on new firm formation, but most of the effect is from spatial spillovers. On the contrary, the ratio of large to small firm in terms of employment size and unemployment rate negatively influence single-unit firm births both within counties and among neighbors. However, there is no significant impact of local financial capital and personal income growth on new firm formation.
Keywords: 330; New firm formation; entrepreneurship; regional dynamics; spatial spillovers; panel data estimation; New England